Quality of life, education and field family in the visual disability since the review theoretical - Prado, Jose Enrique Llamazares de; Gago, Ana Rosa Arias; Alvarez, Maria Antonia Melcon (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
There are few studies that try it relationship between the family and it disability, as well as the importance of it quality of life and the relationship between it education and the family. He present work has as main objective it review of them studies on the paper of them families of them people with diversity functional and its quality of life. Intend to a reflection systematized of the estimate quantitative synthetic of all them studies available, establishing a framework theoretical about the relationship between them families with diversity functional and the quality of life. In this study provides personal estimations about the above mentioned variables. Within the findings, it is evident that the family plays a fundamental role as the first educational core. However, has of combine is efforts for a work joint with them professional with greater involvement in the education, without diminishing the role that exercise them parents, betting is by a well common.